Pretreniranost in relativni energijski deficit - Hadžić, Vedran (Šport (Ljubljana), 2016)
Overtraining is one of the biggest problems of modern sport. If overlooked and not treated it may lead to numerous physiological and psychological changes in athletes, that may be career ending. Current understanding shows that relative energy deficiency may be one of the important risk factors for overtraining. The paper systematically presents both conditions.
Keywords: citokini; cytokines; fatigue; glikogen; glycogen; overreaching; preseganje; pretreniranost; sport; šport; utrujenost